Diving Into Gen Z's Eco-Friendly Business Visions and Entrepreneurial Journeys in Metropolitan Malang - Kirana, Prambayu Candra; Suci, Rahayu Puji; Purwanto, Arief; Supriyadi, Ana Sopanah (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2023)
In today's evolving business realm, sustainable entrepreneurship is paramount, especially in terms of social and environmental accountability. This study explores eco-friendly business visions and entrepreneurial paths among Generation Z in Malang's vibrant Metropolitan Area. Through descriptive analysis, it navigates the aspirations and journeys of young entrepreneurs towards sustainability. Utilizing questionnaire data from 250 participants, the research offers an overview of how education on Sustainable Development Goals (SDGs) and familiarity with the Green Economy intersect with Generation Z's entrepreneurial spirit in Malang. By uncovering significant correlations between SDGs education, Green Economy knowledge, and entrepreneurial intentions, the study provides compelling insights. It also examines the catalytic effects of information technology infrastructure and local government support. Advocating for integrating sustainability principles into education and economic policies, the paper stresses collaborative efforts among businesses, academia, and government entities. Furthermore, it underscores equitable access to technology and the crucial role of local government in nurturing socially and environmentally conscious businesses. Lastly, the paper calls for further research to evaluate the efficacy of SDGs education in equipping Generation Z with entrepreneurial skills for the future.